2007
DOI: 10.1007/s00402-007-0524-3
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular dislocation Rockwood III–V: results of early versus delayed surgical treatment

Abstract: Our results point out that early reconstruction of ACJ-injuries in type III-V avoids the inferior clinical results of delayed reconstructions using a modified Weaver-Dunn-procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
116
1
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 17 publications
0
116
1
15
Order By: Relevance
“…In der Literatur liegt weitgehend Einigkeit darüber vor, dass Verletzungen der Schweregrade Rockwood IV, V und VI operativ zu behandeln sind [4,26]. Uneinigkeit besteht weiterhin über die Therapie von Verletzungen des Grads Rockwood III [2,4,5,24], wobei hier in den letzten Jahren ein Trend zur konservativen Behandlung zu verzeichnen war [30].…”
Section: Hintergrundunclassified
See 2 more Smart Citations
“…In der Literatur liegt weitgehend Einigkeit darüber vor, dass Verletzungen der Schweregrade Rockwood IV, V und VI operativ zu behandeln sind [4,26]. Uneinigkeit besteht weiterhin über die Therapie von Verletzungen des Grads Rockwood III [2,4,5,24], wobei hier in den letzten Jahren ein Trend zur konservativen Behandlung zu verzeichnen war [30].…”
Section: Hintergrundunclassified
“…Wird eine operative Versorgung angestrebt, sollte diese frühelektiv durchgeführt werden, da bei verspäteter Versorgung die biologische Potenz des Gewebes abnimmt und dadurch schlechtere klinische Ergebnisse beobachtet wurden [26,32]. Die Zeitspanne zwischen dem Trauma und der Operation sollte daher mög-lichst kurz sein und 3 Wochen nicht über-schreiten [23].…”
Section: Hintergrundunclassified
See 1 more Smart Citation
“…5 Different surgical methods are described for surgical treatment and could be separated into the following categories: (1) anatomic (reproduction conoid and trapezoid ligaments), (2) nonanatomic (reproduction of a single coracoclavicular [CC] ligament without the use of internal fixation hardware), and (3) nonanatomic open reduction internal fixation using hardware. 6 Weinstein et al 7 and Rolf et al 8 suggest that early surgical treatment of injuries of type III may result in superior clinical outcome than patients undergoing surgical treatment later than 3 months after injury.…”
mentioning
confidence: 99%
“…9 Today, surgeons widely agree that a biological augmentation is required in chronic cases to enhance the healing potential of the torn structures. 8,10,11 Laboratory studies showed that anatomic reconstruction with double graft tendons showed native-like biomechanical properties 12 and clinical data showed promising results. 9,13 With the progress of arthroscopic techniques, arthroscopically assisted techniques for graft reconstruction of the AC joint have been described.…”
mentioning
confidence: 99%